Risks and opportunities: The development of business from migration. A case study in France - Ballesteros, Lily (Cooperativismo & Desarrollo, 2021)
Migration processes increasingly generate new economic and social dynamics. One of these dynamics is migratory entrepreneurship; This article seeks to understand the processes, profile, and relationship with the environment of migrant business owners in the commercialization sector of ethnic or specialized products from their countries of origin, in Paris, France. It was found that elements such as the elaboration of financial, risk and marketing analyses are not performed by most entrepreneurs, increasing the risk of bankruptcy. However, with the increase of French consumers, migrant employment in these types of companies generates a greater obligation for foreign personnel to adapt in order to communicate with their potential customers.
Keywords: migratory entrepreneurship; ethnic consumption; ethnic products; migration